2011
DOI: 10.1002/aic.12555
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of anomalous chloride enrichment related to methane hydrate formation in deep‐sea sediments

Abstract: Anomalous chloride concentration enrichment has been detected in marine sediments comprising methane hydrates (MHs). In this study, we designed an electric circuit system linked to the high-pressure resistance cell in which the chloride ion concentration can be directly measured within reliable accuracy under in situ conditions of the deep-sea floor pressure and temperature. Chloride concentration increased under a fast MH formation rate, but no noticeable concentration change was detected under a relatively l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…However, Figure again confirms that the salting-out exclusion cannot cause a chemical shift change. As mentioned in many studies, the ions that do not participate in hydrate formation should be excluded to the outside of the hydrate phase. , Because the ions remained in the ice (Ih) phase even after the hydrate formation, the surroundings of these excluded ions might not be changed. Thus, the chemical shifts of 23 Na in NaCl (NaOH) + H 2 O + C 3 H 8 and NaCl (NaOH) + H 2 O are expected to be same.…”
Section: Resultsmentioning
confidence: 99%
“…However, Figure again confirms that the salting-out exclusion cannot cause a chemical shift change. As mentioned in many studies, the ions that do not participate in hydrate formation should be excluded to the outside of the hydrate phase. , Because the ions remained in the ice (Ih) phase even after the hydrate formation, the surroundings of these excluded ions might not be changed. Thus, the chemical shifts of 23 Na in NaCl (NaOH) + H 2 O + C 3 H 8 and NaCl (NaOH) + H 2 O are expected to be same.…”
Section: Resultsmentioning
confidence: 99%
“…During hydrate formation, salt ions compete with guest molecules for water molecules, and when salt ions are dissolved by water, the number of hydrogen bonds between water molecules decreases. Therefore, it is difficult for water molecules to form cage clusters through hydrogen bonding interactions and the cage stability is reduced …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is difficult for water molecules to form cage clusters through hydrogen bonding interactions and the cage stability is reduced. 26 Even though numerous experimental studies have demonstrated that electrolytes inhibit hydrate formation, the microscopic mechanisms are still not fully understood because of the time and space constraints of monitoring methods. Many scientists have used MD simulations to investigate hydrate formation because they are an effective tool for revealing the microscopic nature of hydrates at the molecular scale.…”
Section: Introductionmentioning
confidence: 99%